Taksonomi Tujuan Pendidikan dan Evaluasi Hasil Belajar - Mauridhatul Kasanah; Arga Putra Pratama (Pedagogik, 2024)
This research examines the taxonomy of educational objectives through a library research approach, referring to seminal works such as "Taxonomy About Educational Objectives" by Bloom and "Basics of Educational Evaluation" by Zulfa Amirna as primary data sources and secondary sources derived from articles related issues, analyzed using content analysis techniques to evaluate symbolic representations in text and images. This research aims to deepen understanding of the taxonomy of educational objectives which includes the cognitive, affective and psychomotor domains, as well as to develop indicators of student competency achievement. Anderson's revised taxonomy, which introduced categories such as remembering and creating, as well as Bloom and Kathwohl's classification of affective and psychomotor domains, are also reviewed to assess their impact on the assessment of learning outcomes. It is hoped that the results of this research will provide insight for the development of more effective learning and assessment programs, as well as for monitoring and improving student learning progress.